1998
DOI: 10.1212/wnl.50.3.782
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone versus testosterone and testolactone in treating reproductive and sexual dysfunction in men with epilepsy and hypogonadism

Abstract: Antiepileptic drug-induced reductions in serum levels of biologically active testosterone and elevations in serum estradiol (E2) may contribute to sexual dysfunction among men with epilepsy. Treatment using a combination of testosterone and the aromatase inhibitor testolactone may have significantly better effects on sexual function and also seizure frequency than testosterone alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(52 citation statements)
references
References 4 publications
2
48
0
2
Order By: Relevance
“…Alternatively, testosterone might have a biphasic effect on seizures: proconvulsant at higher doses, anticonvulsant at lower doses. Further, notwithstanding the modest antiseizure activity of testosterone in animals (Pesce et al, 2000;Frye et al, 2001b), testosterone itself has not been reported to improve seizures clinically (Herzog et al, 1998). Reductions of seizures were observed only when testosterone was given together with an estrogen synthesis inhibitor, suggesting the estradiol modulation of seizure activity.…”
Section: Resolving Bimodal Effects Of Testosterone On Seizure Susceptmentioning
confidence: 97%
See 2 more Smart Citations
“…Alternatively, testosterone might have a biphasic effect on seizures: proconvulsant at higher doses, anticonvulsant at lower doses. Further, notwithstanding the modest antiseizure activity of testosterone in animals (Pesce et al, 2000;Frye et al, 2001b), testosterone itself has not been reported to improve seizures clinically (Herzog et al, 1998). Reductions of seizures were observed only when testosterone was given together with an estrogen synthesis inhibitor, suggesting the estradiol modulation of seizure activity.…”
Section: Resolving Bimodal Effects Of Testosterone On Seizure Susceptmentioning
confidence: 97%
“…Testosterone is known to produce both proconvulsant and anticonvulsant effects depending on the animal model and the seizure type (Werboff and Havlena, 1968;Thomas and McLean, 1991;Frye and Reed, 1998;Pesce et al, 2000;Mejias-Aponte et al, 2002). Both animal and clinical studies show that testosterone enhances seizure activity by metabolism to estrogens (Isojarvi et al, 1988;Thomas and Yang, 1991;Herzog et al, 1998;Edwards et al, 1999;El-Khayat et al, 2003). Epidemiological data indicate that the occurrence of focal and tonic-clonic epileptic seizures is ~50% higher in intact than in castrated dogs (VMDB Report, 2003).…”
Section: Effect Of Testosterone On Seizure Susceptibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…5,40 This possibility is supported by the previously reported improved seizure control achieved with the adjunctive use of the aromatase inhibitor testolactone or the antiestrogen clomiphene than testosterone alone. 41 (2) Poor seizure control and untreated groups of epileptics exhibited more hormonal abnormalities than the controlled group on AED(s). Many evidences support our findings, including the following: free testosterone levels are usually low in reproductive endocrine disorders that are associated with TLE in men and therefore favor the occurrence of epileptiform activity, 26 testosterone has been found to raise the threshold of some induced seizures in experimental animals, 15,16 and previous studies demonstrated that patients with refractory epilepsy had improved sexual performance after temporal lobectomy.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Estrogens have been shown to have important beneficial effects on bone density, even in males; 8 however, the long-term effects on bone density in men receiving both testosterone supplementation and an anti-estrogen such as anastrozole are uncertain. However, no large-scale studies of anastrozole have been performed in men, and so there is limited information regarding its side effects in this population.…”
Section: Discussionmentioning
confidence: 99%